Unconventional broadening of Rashba spin splitting in a Au2Sb surface alloy with periodic structural defects - Jinbang Hu; Xiansi Wang; Anna Cecilie Åsland; Justin W. Wells (npj Quantum Materials)
Abstract Most Rashba spin splitting experimentally studied so far has ideal lattice with inversion symmetry broken, which limits the possibility to minimize the presence of spin-degenerate carriers near the Fermi level. Here, we report a novel 2D Au2Sb surface alloy decorated with periodic structural defects that exhibits modulation on the Rashba spin-orbit coupling band. Spin- and angle-resolved photoemission spectroscopy reveals a Rashba spin-split band with antiparallel spin polarization, significantly broadened compared to the Au₂Sn surface alloy. From the good agreement between the experimental results and DFT calculations, we identify that the broadening of the Rashba bands comes from variations in Sb atom corrugation induced by the periodic three-pointed star-shaped defects. These periodic defects can shift the energy position of the Rashba bands without breaking the in-plane rotational and mirror symmetries. Our findings highlight the potential to tune spin-dependent properties in 2D materials for spintronic applications.